Thyroid dysfunction in patients of chronic kidney disease - Gupta, Abhishek; K., Kuldeep; Virmani, S. K.; Arora, Mayank (International Journal of Advances in Medicine, 2017)
Background: Thyroid hormones play a very important role in regulating metabolism, development, protein synthesis, and influencing other hormone functions. CKD has been known to affect the pituitary-thyroid axis and the peripheral metabolism of thyroid hormones. We aimed to study the thyroid dysfunction in patients of chronic kidney disease for the prevalence of subclinical hypothyroidism. Methods: This cross-sectional study was conducted at Chhatrapati Shivaji Subharti Hospital and Medical College, Meerut, Uttar Pradesh, India, over a 2 year period. The study group comprised 100 patients with Chronic kidney disease. Free thyroxine (fT3, fT4) and thyroid-stimulating hormone (TSH) were measured. Patients with family history of thyroid disorder or past history of any medication for thyroid disease or history of any surgery or any radiological intervention to thyroid gland were excluded from the study. Results: Of 100 CKD patients, 25 were found to have subclinical hypothyroidism (SCH) and 75 were euthyroid. The mean age in patients with SCH was 47.72±10.09 and in euthyroid patients was 46.11±14.332. 12 males (48%) and 13 females (52%) patients were found to have subclinical hypothyroidism and 49 male (65%), 26 female (35%) patients were euthyroid. Prevalence of SCH was 25% with a mean TSH level of 8.68± 1.84. Conclusions: We observed a high prevalence of SCH in our CKD patients. SCH is an additional risk factor in CKD patients and the present study finds thyroid dysfunction being SCH to be very common in CKD patients and reveals significant association between CKD progression and thyroid dysfunction.